1998
DOI: 10.1023/a:1008464504583
|View full text |Cite
|
Sign up to set email alerts
|

Phase I multicenter study of combined high-dose ifosfamide and doxorubicin in the treatment of advanced sarcomas

Abstract: The dose level of ifosfamide 10 g/m2 and doxorubicin 90 mg/m2 with supportive GM-CSF is manageable in a multicenter setting and should be further tested in regular phase II trials, including patients with gynecological and soft-tissue sarcomas. Transient toxicity with myelosuppression should be accepted in order to obtain a high antitumor activity of this regimen and a potential improvement in survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2003
2003
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 22 publications
1
21
0
3
Order By: Relevance
“…In a previous phase I trial, we identified the maximum tolerated dose levels for combined administration of ifosfamide and doxorubicin (Leyvraz et al, 1998). The phase II trial herein presented was required to confirm the increased response rate suggested in that previous trial.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a previous phase I trial, we identified the maximum tolerated dose levels for combined administration of ifosfamide and doxorubicin (Leyvraz et al, 1998). The phase II trial herein presented was required to confirm the increased response rate suggested in that previous trial.…”
Section: Discussionmentioning
confidence: 90%
“…In a previous study, we defined the maximum tolerated dose of doxorubicin combined with ifosfamide, administered every 3 weeks and supported by haematopoietic growth factors (Leyvraz et al, 1998). The maximum tolerated dose of doxorubicin was 60 mg m À2 with ifosfamide at 12 g m À2 and could be increased to 90 mg m À2 with ifosfamide at 10 g m À2 .…”
mentioning
confidence: 99%
“…Two commonly used chemotherapeutic agents, doxorubicin and ifosfamide, have response rates ranging from 17 to 33% as single-agent therapy [83][84][85][86] and 55 to 66% when used in combination [87][88][89]. However, few of the trials have combined both drugs at effective doses.…”
Section: Chemotherapymentioning
confidence: 99%
“…The main toxicity was myelosuppression, and despite the use of G-CSF, febrile neutropenia was encountered in 31% of all cycles [67]. Leyvraz et al [68] published a study of doxorubicin (90 mg/m 2 ) plus ifosfamide (10 g/m 2 ) in combination with G-CSF, which resulted in a response rate of 55%. Of note, this combination induced severe bone marrow toxicity, given World Health Organization grade 4 leukopenia in 58%, grade 3-4 thrombopenia in 42%, and anemia in 31% of cycles.…”
Section: Ifosfamide In Combination Therapymentioning
confidence: 99%